Just one year - Forman, Gayle (New York : A Penguin Random House Company, 2013)
Picking up where Just One Day ended, Just One Year tells Willem's side of the story. After spending an amazing day and night with Allyson in Paris that ends in separation, Willem and Allyson are both searching for one another. His story of their year of quiet longing and near misses is a perfect counterpoint to Allyson$1 (Bs own as Willem undergoes a transformative journey, questioning his path, finding love, and ultimately, redefining himself.s
Keywords: VOYAGES AND TRAVELS